Aspects of the influence of commercial law on corporate ethical practices in Indonesia - Noh Chang Dong; Ramlani Lina Sinaulan; Joko Sriwidodo (International Journal of Law and Society, 2025)
Analyzing the implications of business law on business ethics practices in Indonesia using library research methods. Data was collected from various literature sources relevant to the research topic. The results show that business law has an important role in shaping business ethics in Indonesia. Business law regulates the rights and obligations that arise from agreements and agreements in business practices. Factors underlying business law such as developments in national development, business ethics, internal and external factors and legal awareness influence the implementation of business law in ethical and responsible business practices. Solutions that can be provided to improve the implementation of business law and ethical business practices in Indonesia are by strengthening regulations, effective law enforcement, education, government collaboration with business, accountability, and the formation of an independent supervisory body. In improving the implementation of business law, it is hoped that it can create a fair, transparent and integrity business environment and make a positive contribution to economic development and social welfare in Indonesia.